KARAKTERISTIK DAN DAYA JERAP POLUTAN ARANG AKTIF DARI BATANG KENAF (Hibiscus cannabinus L.) - Muhammad Sadir; Dede Hermawan; Ismail Budiman; Gustan Pari; Jajang Sutiawan (BRIN Publishing, 2022)
Kenaf is one of the plants fiber that deries kenaf stems into biomass waste. The utilization of kenaf stem waste could be usedas an ingredient for making activated charcoal. The purpose of this study was to analyze the effect of activation temperature on theproperties of activated charcoal and its pollutant adsorption capacity based on Indonesian Standart (SNI 06-3037-1995) ontechnical activated charcoal. Activated charcoal was made of hydro charcoal soaked into H3PO4 and K2CO3 for 24 hours, thenphysically activated at temperatures 600, 700, and 800°C. The results showed that all activated charcoal met the technical activatedcharcoal quality requirements set by the SNI 06-3730-1995 standard for parameters moisture content and volatile matter content,but only some activated charcoal could meet the requirements for ash content, bound carbon and iodine adsorption capacity. Activatedcharcoal formaldehyde, ammonia, chloroform, and benzene adsorption capacity increases with increasing activation temperature. Thebest activated charcoal by yield and the adsorption iodine using K2CO3 activator was at 700°C, and H3PO4 activator was at600°C, while the best adsorption activated charcoal formaldehyde, ammonia, chloroform, and benzene at temperature 800°C.